Antigen-specific T cell phenotyping microarrays using Grating Coupled Surface Plasmon Resonance Imaging and Surface Plasmon Coupled Emission - Rice, James M. (2011)
The circulating population of peripheral T lymphocytes obtained from a blood sample can provide a large amount of information about an individual's medical status and history. Recent evidence indicates that the detection and functional characterization of antigen-specific T cell subsets within the circulating population may provide a diagnostic indicator of disease and has the potential to predict an individual's response to therapy. In this report, a microarray detection platform that combines grating-coupled surface plasmon resonance imaging (GCSPRI) and grating-coupled surface plasmon coupled emission (SPCE) fluorescence detection modalities was used to detect and characterize CD4(+) T cells. The microspot regions of interest (ROIs) printed on the array consisted of immobilized antibodies or peptide loaded MHC monomers (p/MHC) as T cell capture ligands mixed with additional antibodies as cytokine capture ligands covalently bound to the surface of a corrugated gold sensor chip. Using optimized parameters, an unlabelled influenza peptide reactive T cell clone could be detected at a frequency of 0.1% in a mixed T cell sample using GCSPRI. Additionally, after cell binding was quantified, differential TH1 cytokine secretion patterns from a T cell clone cultured under TH1 or TH2 inducing conditions was detected using an SPCE fluorescence based assay. Differences in the secretion patterns of 3 cytokines, characteristic of the inducing conditions, indicated that differences were a consequence of the functional status of the captured cells. A dual mode GCSPRI/SPCE assay can provide a rapid, high content T cell screening/characterization tool that is useful for diagnosing disease, evaluating vaccination efficacy, or assessing responses to immunotherapeutics.